2012
DOI: 10.7314/apjcp.2012.13.7.3427
|View full text |Cite
|
Sign up to set email alerts
|

TNM Stages and Prognostic Features of Colorectal and Mucinous Adenocarcinoma Patients: a Meta Analysis

Abstract: Aim: The significance of the mucinous adenocarcinoma in TNM staging and prognosis for colorectal tumor patients is still controversial. The aim was to provide a meta-analysis for TNM staging and prognostic features of colorectal tumors. Methods: 30 individual case-control studies were finally included into this meta-analysis, involving a total of 444,489 cancer cases and 45,050 mucinous adenocarcinomas, of relations with TNM staging and prognostic features. Results: Compared to non-mucinous adenocarcinoma pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 30 publications
3
11
0
Order By: Relevance
“…Similarly, Zeng et al (1996) found that MMP-9 levels were 5-fold greater in CRC compared to the normal mucosa (Zeng et al, 1996). Other studies also found a similar relationship between MMP-9 and metastasis (Yamada et al, 2010;Chen et al, 2012;Herszényi et al, 2012). The contradictory results regarding MMP-9 expression and its relationship with invasion, lymph node involvement, and distant metastasis were because of the different sources of the samples.…”
Section: Mmp-9 Expression In Crcmentioning
confidence: 75%
See 2 more Smart Citations
“…Similarly, Zeng et al (1996) found that MMP-9 levels were 5-fold greater in CRC compared to the normal mucosa (Zeng et al, 1996). Other studies also found a similar relationship between MMP-9 and metastasis (Yamada et al, 2010;Chen et al, 2012;Herszényi et al, 2012). The contradictory results regarding MMP-9 expression and its relationship with invasion, lymph node involvement, and distant metastasis were because of the different sources of the samples.…”
Section: Mmp-9 Expression In Crcmentioning
confidence: 75%
“…Interestingly, signet ring cells were present almost exclusively in females (90%; P = 0.0177). Although previous studies found no clear relationship between the presence of mucus and survival, most studies agree that these patients have worse prognosis and shorter survival compared to patients with non-mucinous tumors (Henrique-Filho et al, 2004;Chen et al, 2012;Numata et al, 2012).…”
Section: Clinical Featuresmentioning
confidence: 88%
See 1 more Smart Citation
“…Currently, mucinous histology does not influence treatment decision-making for this cancer [11]. However, evidence has suggested that a MCC is a biologically distinct disease requiring special clinical consideration and treatment strategy [121314]. This study aims to investigate the clinicopathological features of MCCs and to identify the relationship between this histology and patients' oncologic outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18] They have also been associated with a worse prognosis. 15,[19][20][21] However, all studies of mucinous adenocarcinomas have focused on either nonmetastatic or unresectable stage IV colorectal cancers. No study has evaluated the impact of mucinous characteristics on candidates for LR of CRLM.…”
mentioning
confidence: 99%